2014
DOI: 10.1002/cncr.29149
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and mood of patients and family caregivers during hospitalization for hematopoietic stem cell transplantation

Abstract: Background To investigate the impact of hospitalization for hematopoietic stem cell transplantation (HCT) on patients’ and family caregivers’ (FC) quality of life (QOL) and mood. Methods We conducted a longitudinal study of patients hospitalized for HCT and their FC. At baseline (6 days pre-HCT), day+1, and day+8 of HCT, we assessed QOL (Functional Assessment of Cancer Therapy-Bone Marrow Transplantation FACT-BMT), and mood (Hospital Anxiety and Depression Scale HADS). We administered the SF-36 to examine FC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
191
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(210 citation statements)
references
References 27 publications
11
191
3
5
Order By: Relevance
“…However, a reduction is observed over the six months after transplantation in both groups. This result is confirmed by a study 21 carried out in Massachusetts, which showed the symptom of pain as one of the most frequently reported during treatment in both patients undergoing allogeneic and autologous HSCT, with no statistically significant differences between the HSCT types.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, a reduction is observed over the six months after transplantation in both groups. This result is confirmed by a study 21 carried out in Massachusetts, which showed the symptom of pain as one of the most frequently reported during treatment in both patients undergoing allogeneic and autologous HSCT, with no statistically significant differences between the HSCT types.…”
Section: Discussionsupporting
confidence: 55%
“…Studies conducted in the Netherlands and the United States with adult patients confirm this result. [19][20][21] Higher education fosters understanding questions related to treatment, especially with regard to the guidelines during hospital stay and after discharge. It is essential that this understanding occurs, making the patient predisposed to developing self-care and active participation in their attempt for succeeding in their therapeutic path and to recover their life activities.…”
Section: Discussionmentioning
confidence: 99%
“…En la población general con trastornos de ansiedad y depresión, el 12,6% ha tenido estudios primarios, 42,8% secundaria y 44% educación superior (13) . Si bien se ha reportado hasta 16% de depresión y 21% de ansiedad en cuidadores primarios de pacientes hematológicos (21) y cifras similares en parálisis cerebral infanti l y asma (6,17,22,23) , no existen datos nacionales ni extranjeros en pacientes hospitalizados, salvo en unidades de prematuros (24,25) . Nuestra investi gación no ha considerado cuidadores de pacientes con una patología específi ca, aunque cerca del 40% fueron neurológicos con postración crónica, como la parálisis cerebral infanti l. Tabla 2.…”
Section: Depresión Y Ansiedad En Cuidadores Primarios En El Institutounclassified
“…It is now well-known that caregiving negatively impacts the life of the caregiver (67)(68)(69).Caregiving leads to a higher risk of mortality (70) and resulted in a significant and substantial burden, restricted roles and activities, and increased psychosomatic (71), anxious, or depressive symptoms (72), and lower QoL (73).…”
Section: The Quality Of Life Of the Caregiversmentioning
confidence: 99%